The Free Chimeric Great Toe and Second Toe Pulp Flap for Reconstruction of Complex Digital Defects - Luigi Troisi, MD, PhD, FEBOPRAS, FACS; Stephanie Hili, MD, FRCS(Eng); Alessandro Mastroiacovo, MD; Francesco Zanchetta, MD; Macarena Vizcay, MD; Giorgio E. Pajardi, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. Toe-to-hand transfers have been extensively described in the literature and are nowadays a fairly common tool in the armamentarium of the reconstructive hand surgeon. Despite this, little has been reported about the chimeric use of flaps based on the first dorsal metatarsal artery. We report here an innovative technique for harvesting the great toe and second toe pulps in a chimeric fashion, which we have found particularly useful in reconstructing digital defects in cases of complex hand trauma involving multiple digits. We describe the technique for flap harvest and illustrate its usefulness through 4 cases of complex hand trauma where we have successfully used it to retain length and function of the digits.